Case study: OYO Hotels / Azrin Izzat Abdul Bari … [et al.] - Abdul Bari, Azrin Izzat; Othman, Ilyanie Natasha; Mohd Sani, Nur Kaymilia; Ku Mohd Fauzi, Ku Farisha Nabilah; Wan Ismail, Wan Nur Husnina Athirah (2022)
OYO Hotels is India's fastest growing branded network of inexpensive hotels, created in 2012 by young entrepreneur Mr. Ritesh Agarwal. OYO hotels have quickly spread around the globe. Similarly, OYO has attempted to be present in major metros, regional hubs, leisure destinations, and pilgrimage towns. However, during and after the Covid-19 pandemic, OYO Hotels are facing huge problem and challenges in their business. So, we took this opportunity to create a case study and applied in practical situations using Business Model Canvas (BMC). The problems that OYO Hotels faced are poor service quality, having a very tight margin, still making loses and receive low number of bookings. We could see the findings and outcomes that needed to be highlighted in this study. After a few years of operation, OYO Hotels has gotten a large number of negative comments and reviews from guests who were dissatisfied with their service. Some of the reviews said about the poor service quality. The review has been attached with proof that their service can be improved. They also find out that they had a very tight margin. Even though they can live with their current margin, they still can improve their margin by using taking advantage of the Covid-19 pandemic. Besides, OYO hotels still making loses while operating. They can improve this problem by changing their target market. Last but not least, OYO hotels are facing low number of bookings. They should push their marketing department to create a better advertisement.